The mortality-incidence ratio as an indicator of five-year cancer survival in metropolitan Lima - Stenning Persivale, Karoline Andrea (2018)
Introduction: The Mortality–Incidence Ratio complement [1 – MIR] is an indicator validated in various populations to estimate five-year cancer survival, but its validity remains unreported in Peru. This study aims to determine if the MIR correlates directly with five-year survival in patients diagnosed with the ten most common types of cancer in metropolitan Lima. Materials and methods: The Metropolitan Lima Cancer Registry (RCLM in Spanish) for 2004–2005 was used to determine the number of new cases and the number of deaths of the following cancers: breast, stomach, prostate, thyroid, lung, colon, cervical, and liver cancers, as well as non-Hodgkin’s lymphoma and leukaemia. To determine the five-year survival, the five-year vital status of cases recorded was verified in the National Registry of Identification and Civil Status (RENIEC in Spanish). A linear regression model was used to assess the correlation between [1 – MIR] and total observed five-year survival for the selected cancers. Results: Observed and estimated five-year survival determined by [1 – MIR] for each neoplasia were thyroid (66.7%, 86.7%), breast (69.6%; 68%), prostate (64.3%, 63.8%) and cervical (50.1%, 58.5%), respectively. Pearson’s r coefficient for the correlation between [MIR – 1] and observed survival was = 0.9839. Using the coefficient of determination, it was found that [1 – MIR] (X) captures the 96.82% of observed survival (Y). Conclusion: The Mortality–Incidence Ratio complement [1 – MIR] is an appropriate tool for approximating observed five-year survival for the ten types of cancers studied. This study demonstrates the validity of this model for predicting five-year survival in cancer patients in metropolitan Lima.